Why Does Tobacco Agriculture in Thailand Persist? - Promphakping, Buapun; Chamaratana, Thanapauge; Somaboot, Pornpen; Weeranakin, Pattaraporn; Promphakping, Ninwadee; Phatchaney, Kritsada (Forest and Society, 2021)
The rigorous tobacco controls advocated by both international policy players and national government are foreseen to lowering demand in tobacco consumption, and consequently, the contraction of tobacco agriculture. This paper seeks to reveal why tobacco agriculture, albeit with the declining trend of tobacco farms, continues to persist. Theoretical guiding the investigation is based on the institutional arrangement of contract farming system, the idea that derived from New Institution Economics, and farmers’ striving to attain livelihoods. The study adopts qualitative methods, utilising purposive sampling, with 53 tobacco farmers recruited from four provinces, namely Phrae, Phetchabun, Roi-et and Nongkhai, who took part in four focus group discussions. In addition, in-depth interviews were conducted with two provincial agricultural promotion officers, three provincial excise officers and four staff members of the local office of the Thailand Tobacco Monopoly. The data was analysed using content analysis. This paper found that supportive institutional arrangements, the adaptation of communities and households creating a favourable environment and the emergence of new markets for roll-your-own cigarettes are contributing to the persistence of tobacco agriculture. In light of tobacco control, two policy measures are proposed. First, the regulations for roll-your-own cigarette industries – both smallholders and manufacturers – must be revised and instituted. Second, to encourage tobacco farmers to move away from tobacco growing, institutional support for alternative crops, such as price guarantees, inputs and technical support should be provided in the same manner that the tobacco growers currently receive.